PENGARUH MOTIVASI KERJA DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. PEGADAIAN KANWIL VII DENPASAR - I Putu Agung Galih Pradnyana Putra; I Ketut Merta; Ni Ketut Ayu Sudha Sucandrawati (Nusantara Hasana Journal, 2022)
Pegadaian is one of the non-bank financial institutions in Indonesia that is owned by a BUMN. Work motivation, leadership in the organization is deemed necessary to see the performance of employees at PT. Pegadaian Regional Office VII Denpasar. This study aims to determine the effect of work motivation and leadership on the performance of employees of PT. Pegadaian Regional Office VII Denpasar. The research method used is quantitative with a population of 1400 employees in all Units and UPCs in Denpasar. In the sampling technique determined N = (25 x 2 Independent variables), then the number of samples to be studied is 50 respondents. The data collection technique in this research is using a questionnaire with purposive sampling technique. The data in this study were processed using multiple linear regression test with SPSS program. The results of this study indicate that work motivation has no significant effect on performance, it is shown that the tcount of the work motivation variable has a negative value of -0.934 with a significance value of 0.355. This significance value is greater than the significance limit value, which is 0.05 which is declared insignificant. For the leadership variable, the tcount value of 4.121 can be obtained with a significance value of 0.000. This significance value is smaller than the significance limit value, which is 0.05. Leadership has a positive and significant effect on performance. Work motivation and leadership have a simultaneous positive effect on performance with a calculated F value of 8.658 with a significance level of 0.001 less than 0.05. The determinant coefficient of 26.9% of performance is influenced by work motivation and leadership variables, while the remaining 73.1% is influenced by other variables not analyzed in this study.